ABC‐type diffuse large B‐cell lymphoma presenting as rotator cuff tendinopathy: A diagnostic dilemma and review of the literature. Issue 2 (20th January 2020) - Beutler, Bryce David; Krishan, Rohee; Parafianowicz, Pawel; Ulanja, Mark B.; Elliott, Christie; France, Joel; Islam, Raheel; Gullapalli, Nageshwara
Abstract: Diffuse large B‐cell lymphoma often presents with extranodal manifestations involving the musculoskeletal system. Shoulder pain is particularly worrisome for malignancy. Individuals presenting with refractory upper extremity complaints should undergo a prompt and thorough evaluation for cancer, as a delay in diagnosis can result in an unfavorable outcome. Abstract : Diffuse large B‐cell lymphoma often presents with extranodal manifestations involving the musculoskeletal system. Shoulder pain is particularly worrisome for malignancy. Individuals presenting with refractory upper extremity complaints should undergo a prompt and thorough evaluation for cancer, as a delay in diagnosis can result in an unfavorable outcome.